National and ınternational advances in physics education in the last three years: A thematic review - Çepni, Salih; Ormancı, Ümmühan; Kaçar, Sevinç (Journal of Turkish Science Education, 2017)
For research areas to advance, researchers are required to carry out studies that are in line with the inadequacies in the field and to have a grasp of the studies in the field. One of the most important means of identifying inadequacies in a field is to review studies between certain years. In this sense, it is important to analyze the publications of significant journals in physics education. The purpose of this study is to conduct a thematic review of the literature related to physics education studies in certain journals published within the scope of Social Sciences Citation İndex in 2013-2015. The articles obtained from the literature were analyzed using a generated matrix. The matrix consists of general specifications (type of journal, years and demographic properties) and content sections (aims, research methods, variables, samples, physics subjects and results). According to the findings, in terms of physics concepts, the studies were conducted mostly on the concept of energy and included mostly undergraduate student participants. Regarding the results, it is suggested, both in physics and science education studies, that materials that are to be used with approaches, such as context-based learning, inquiry-based leaning, and argumentation-based learning, need to be enhanced and that additional studies that investigate the effects of these approaches on learning environments are needed.